If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-1x) + 44 = 0 Remove parenthesis around (-1x) 3 * -1x + 44 = 0 Multiply 3 * -1 -3x + 44 = 0 Reorder the terms: 44 + -3x = 0 Solving 44 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-44' to each side of the equation. 44 + -44 + -3x = 0 + -44 Combine like terms: 44 + -44 = 0 0 + -3x = 0 + -44 -3x = 0 + -44 Combine like terms: 0 + -44 = -44 -3x = -44 Divide each side by '-3'. x = 14.66666667 Simplifying x = 14.66666667
| 1k-3k+9=37 | | 6-4x=90 | | f(3)=1+x | | 4x+1-3x=7+6 | | 9x-4=(2x+3) | | 2(-x)+5x=2x+12 | | 20-4x=-20 | | f(0)=1-5x+10 | | .66y+2=.33y | | 2a(3a-5)=0 | | 2(-x)-3(-x)=2(-x)+18 | | x=y/18 | | f(x+6)=2x-7 | | f(-2)=2x*-5x-1 | | 4(2a+6)=3(4a-8) | | 33=-4x+5 | | 2(x+3)+3x-x=x+16 | | 10=11+11y | | 5c+13=16 | | 25-7a=28a-4a | | f(2)=3x*2-3x-3 | | 15x-5y+18=20 | | 9q-24=9q-12 | | 6cos^2x-7cosx-3=0 | | 5x+35=135 | | 5.8z-5=4.8z-5 | | 2x+x+3=3x+5 | | -5x-7=9x+15 | | -7-8n=47 | | 5=18 | | 3(-x)+5x=x+9 | | 2(-x)+5x=x+9 |